Orchiopexy through a single high transverse scrotal incision - Khirallah, Mohammad G. (Afr J Paediatr Surg, 2015)
BACKGROUND: Palpable Undescended Testis (PUT) represents a common paediatric problem in many premature and some mature infants. There are several surgical techniques to correct PUT either through combined inguinal and scrotal incision or single transverse scrotal incision. This study assessed single high transverse scrotal incision for the management of PUT as regards to feasibility, postoperative success and final cosmetic results. MATERIALS AND METHODS: One hundred twenty patients were managed at the Paediatric Surgery Department of Tanta University Hospital with PUT during the period from March 2010 to March 2014. They were all operated at the age of 6-12 months. We excluded recurrent cases, and cases older than 12 months. Through high transverse scrotal incision, the layers were divided, and the canal entered through the external ring, dissecting the PUT and bringing it through the incision. Hernia sac, if present, was ligated at the neck. Creation of the dartos pouch was then made through the same incision. All infants were followed-up at 1 month, 2 months and 6 months to detect any re-ascended cases, testicular atrophy and the final cosmetic appearance. RESULTS: A total of 140 PUTs were operated upon in 120 patients. PUT was bilateral in 20 patients, right-sided in 65 cases and left-sided in 35 cases. Thirty testes were located at the external ring; the others were located within the inguinal canal. No cases needed a redo operation, and there was no case of postoperative testicular atrophy. CONCLUSION: Single high transverse incision was sufficient to deal with PUT especially, in young infants (age 6 months) with no need for conversion in most cases to the traditional two incisions technique, and good long term follow-up and a better cosmetic results.